[Rezension von: McMahan, David L. [Hrsg.], Meditation, Buddhism, and science] - Prohl, Inken (Religion, 2018)
(2018). Meditation, Buddhism, and Science, edited by David McMahan and Erik Braun, New York, Oxford University Press, 2017, xi + 253pp., US$24.95 (paperback), ISBN 978 0 1904 9579 4. Religion: Vol. 48, Thematic Issue on The Marketization of Religion. Guest Editors: François Gauthier and Tuomas Martikainen, pp. 526-529.
Gesehen am 20.09.2018
Keywords: Rezension